TRANSLATIONAL ENHANCERS FOR PLANT GENE ENGINEERING - A. V. Kochetov; E. A. Filipenko; O. G. Smirnova; V. K. Shumny (Вавиловский журнал генетики и селекции)
Transgenic plants are often used in both fundamental and applied research. It is well known that transgene expression strongly depends on the genetic construct design. In particular, 5′-UTR is an important element, as it influences mRNA translation efficiency and the protein synthesis rate. The review considers 5′-UTR features controlling translation efficiency in plant cells and some useful translational enhancers.